Evaluating Housing Characteristics Associated With Childhood Lead Exposure in Providence, Rhode Island. Issue 2 (March 2022) - Vasil, Taylor-Marie; Rogers, Michelle L.; Singleton, Cindy; Vivier, Patrick M.
Abstract : Objective: This research aims to take an in-depth look into the child, housing, and neighborhood characteristics associated with Providence children's likelihood of having elevated blood lead levels (BLLs). Design and Setting: The 2019 Providence, Rhode Island, Property Tax Assessor's database, containing each property owner's address, was geocoded and spatially joined with the 2017-2019 blood lead tests for children aged 0 to 6 years from the Rhode Island Department of Health. Main Outcome Measures: The prevalence of elevated BLLs (≥5 μg/dL) overall, as well as by property type, number of properties owned, owner occupancy, assessed value, and neighborhood rates of old housing and poverty, was computed. We assessed the relationship between having elevated BLLs and these housing and neighborhood characteristics, adjusting for gender, age at test, and test method. Results: We found that, compared with children living in properties with landlords who owned only one property, children living in properties with landlords who owned 4 or more properties had lower odds of having elevated BLLs (odds ratio = 0.98; 95% confidence interval, 0.97-0.99). The proportion of houses built pre-1950 in the neighborhood was associated with increased odds of elevated BLLs. There was no significant association between owner-occupancy status and property type with children having elevated BLLs. Conclusions: Children living in properties with landlords who owned 4 or more properties were less likely to have elevated BLLs. This association may suggest that the current lead legislation is having some impact, but public health efforts should address lead exposure in properties that are currently exempt from the law.